How work stress influence turnover intention among Chinese local undergraduate university teachers: the mediating effect of job burnout and the moderating effect of self-efficacy - Pei, Shuimei; Wang, Shichao; Jiang, Ruixuan; Guo, Jianpeng; Ni, Jianchao (Frontiers in Public Health, 2024)
Background: Turnover intention is one of the common disturbances that affect the career development and management of university teachers. With an aim to solve this thorny issue, the study examined the associations between turnover intention and work stress among local undergraduate university teachers in China.Methods: A questionnaire survey was carried out on 7565 local university teachers. Initially, confirmatory factor analysis was employed to validate the reliability and validity of the scale.Subsequently, descriptive statistics and correlation analyses were conducted. Following this, a latent moderated structural equation (LMS) was used to explore the relationship among work stress, job burnout, self-efficacy, and turnover intention. Moreover, the bias-corrected Bootstrap method was applied to further examine the mediating effects, moderating effects and moderated mediating effects in the model.The hypothesized moderated mediation model was verified significant. Work stress directly and positively predicted job burnout and turnover intention, with job burnout serving a partial mediating role between work stress and turnover intention. Additionally, self-efficacy negatively moderated the direct impact of work stress on job burnout, as well as the mediating effect of job burnout. As the self-efficacy of university teachers increased, the direct effect of work stress on job burnout and the mediating effect of job burnout decreased.This study expanded the research on the antecedent variables of university teachers' turnover intention and revealed the individual contingency mechanism by which work stress affected turnover intention: the negative moderating effect of self-efficacy. Work stress induced university teachers' turnover intention, and this phenomenon was more obvious for faculties with low self-efficacy. Administrators of local undergraduate universities need to rationalize the allocation of teachers' job responsibilities and pay attention to the negative consequences of work stress in order to reduce turnover intentions. Particular attention should be paid to enhance teachers' self-efficacy. The findings of this study can provide in-depth recommendations for university faculty management and policy making, which can help shape a working atmosphere more conducive to teaching and research, thus enhancing the overall quality and competitiveness of faculty members within universities.